PENERAPAN METODE PROJECT-BASED LEARNING DALAM PEMBELAJARAN AL-QUR'AN SURAH AL-FALAQ - Utia Lina Anggriani; Irja Putra Pratama (Guruku: Jurnal Pendidikan Profesi Guru, 2025)
This study aims to improve students' learning outcomes in the subject of "Senang Bisa Menulis Surah Al-Falaq" by implementing the Project Based Learning (PJBL) method in Class II at SDN Lubuk Tua, Muara Kelingi. The research was conducted using a classroom action research approach, which involved two cycles of implementation. The data were collected through observations, tests, and reflections. The findings indicate that before the PJBL method was applied, the students' learning outcomes were low, with an average score of 46, and most students were in the "insufficient understanding" category. In Cycle I, there was an increase in the average score to 62, with some students showing better participation, but the results still did not meet the expected target. In Cycle II, after improvements were made in student motivation and group interactions, the average score rose significantly to 72, and the majority of students reached the "good" category. The results demonstrate that the PJBL method is effective in enhancing students' understanding and engagement in learning. Thus, PJBL is recommended as a method to improve learning outcomes in Islamic education for elementary school students.